2007
DOI: 10.1534/genetics.106.065565
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles for β1,4-N-Acetlygalactosaminyltransferase-A in Drosophila Larval Neurons and Muscles

Abstract: Adult Drosophila mutant for the glycosyltransferase b1,4-N-acetlygalactosaminyltransferase-A (b4Gal-NAcTA) display an abnormal locomotion phenotype, indicating a role for this enzyme, and the glycan structures that it generates, in the neuromuscular system. To investigate the functional role of this enzyme in more detail, we turned to the accessible larval neuromuscular system and report here that larvae mutant for b4GalNAcTA display distinct nerve and muscle phenotypes. Mutant larvae exhibit abnormal backward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 44 publications
(50 reference statements)
1
32
0
Order By: Relevance
“…15 Drosophila mutants deficient in B4GALNTA have defects in behavior and in the neuromuscular system. 16 In the present study, we hypothesized that B4GALNT3 may be involved in the pathogenesis of NB development.…”
Section: ␤14-n-acetylgalactosaminyltransferase III (B4galnt3)mentioning
confidence: 89%
“…15 Drosophila mutants deficient in B4GALNTA have defects in behavior and in the neuromuscular system. 16 In the present study, we hypothesized that B4GALNT3 may be involved in the pathogenesis of NB development.…”
Section: ␤14-n-acetylgalactosaminyltransferase III (B4galnt3)mentioning
confidence: 89%
“…GlcNAc-containing carbohydrate and GAG scaffolds (e.g., chitin, hyaluronic acid [HA], heparin) and PG (e.g., heparin sulfate, chondroitin sulfate) are components of neuronal and muscle ECM, and concentrated within the specialized synaptic cleft matrix at the NMJ and other synapses in multiple species (Martin 2003b;. It was recently shown that loss of GlcNAc transferase alters In Drosophila NMJ synaptic structure, function, and locomotory behavior (Haines and Stewart 2007), independently demonstrating GlcNAc-mediated interactions have roles in synaptic maturation.…”
Section: Mtg Is a Secreted Protein Predicted To Bind Extracellular Symentioning
confidence: 99%
“…No more than two muscles were measured from a single larvae. Sarcomeres were measured from gray scale intensity plots across phalloidinstained sarcomeres (see Figures 2 and 3; Haines and Stewart, 2007), sarcomere size being the distance between adjacent peaks. In cases where the graph did not clearly show a single peak for a sarcomere, the center of the high-intensity region was selected by eye as the peak value.…”
Section: Muscle Measurementsmentioning
confidence: 99%
“…The spacing of the F-actin bands can be analyzed by graphing gray scale intensity across phalloidin-stained sarcomeres, and Z-bands are represented as peaks. The distance between peaks can be used as a measure of sarcomere size, and the width of the curve can be used to assess the width of the F-actin band ( Figure 2; Haines and Stewart, 2007). We examined the spacing of the F-actin bands along muscle 6, segments 3 or 4; when the banding pattern across the entire length of the muscle was intact (yw, n ϭ 8; Dg 248 , n ϭ 8; Dg 323 /Dg 248 , n ϭ 8; Dg 323 , n ϭ 6).…”
Section: Dystroglycan Mutant Muscles Have Altered Sarcomere Sizementioning
confidence: 99%